THE DIFFERENCES OF ANALYTICAL THINKING SKILLS IN PROBLEM BASED LEARNING MODEL EQUIPPED BY MIND MAP WITH CONVENTIONAL CLASS TOWARDS SCIENCE FIRST GRADE STUDENTS OF SMA AL ISLAM 1 SURAKARTA IN THE ACADEMIC YEAR 2013/2014 - Bowo Sugiharto, Henri Nelista Mei Dawati,Puguh Karyanto (Pendidikan Biologi, 2015)
The research aims to find out the differences of the analytical thinking skills in Problem Based Learning model equipped by Mind Maps with conventional class towards science first grade students of SMA Al Islam 1 Surakarta in the academic year 2013/2014. The research was quasi-experimental research with posttest only non-equivalent control group design. The population of the research was all of science first grade students SMA Al Islam 1 Surakarta in the academic year 2013/1014. The techniques of collecting data are test and non-test methods. The form of test method is essay, whereas the forms of non-test method are documentation and observation sheets. Data were analyzed by T-test, Kolmogorof-Smirnov test, and Levene's test with SPSS 16. The results show that there are some differences in the analytical thinking skills in Problem Based Learning model equipped by Mind Maps with conventional class towards science first grade students of SMA Al Islam 1 Surakarta in the academic year 2013/2014. The application of the learning model of Problem Based Learning equipped by Mind Map has the higher average than the application of conventional methods. The observation results indicate the resemblance of Problem Based Learning with the Mind Map syntax. The result of the T-test shows a significant difference (sig <0.05) towards the analytical thinking skills between the control class and the experimental class T-test value is 0.009. The results of this study can be concluded that there are some differences in the analytical thinking skills towards Problem Based Learning model equipped by Mind Maps with conventional class towards science first grade students of SMA Al Islam 1 Surakarta in the academic year 2013/2014. Referring to the differences of the analytical thinking skills mean, the application of Problem Based Learning model equipped by Mind Maps can affect the analytical thinking skills students to be better. Keywords: analytical thinking skills, problem based learning, mind map